Asuhan Keperawatan Jiwa pada Pasien dengan Halusinasi Pendengaran Di Wisma Nuri Rumah Sakit Jiwa Prof Dr HB Saanin Padang - Halmi Azzahra; Dwi Happy Anggia Sari; Vivi Yuderna; Ramaita Ramaita (CV. ITTC INDONESIA, 2026)
World Health Organization (WHO) data for 2023 shows that the number of people with mental disorders worldwide continues to increase, reaching 970 million people in 2023 and predicted to exceed 1.1 billion by 2024. One of the symptoms that frequently emerges is hallucinations, where sufferers experience false sensations without any real external stimulus. This case study aims to describe psychiatric nursing care for patients with a diagnosis of auditory hallucinations at RSJ Prof. Dr. HB Sa’anin Padang in 2026. The research method used a case study through a nursing process approach consisting of assessment, diagnosis, intervention, implementation, and nursing evaluation. The results of the assessment showed that the patient experienced auditory hallucinations, social isolation, and self-care deficits triggered by social stressors such as divorce trauma and economic problems. Interventions were carried out through the application of Implementation Strategy (SP) 1-4 which included rebuking (menghardik), medication adherence, conversation, and scheduled activities. Evaluation results after five days of action showed an increase in the client's ability to control hallucinations independently and improvements in self-care independence. In conclusion, the consistent application of implementation strategies is effective in reducing hallucination symptoms in clients. This study is expected to serve as a reference for nursing staff in optimizing comprehensive psychiatric nursing care for clients with sensory perception